Enhanced T-Cell Immunogenicity and Protective Efficacy of a Human Immunodeficiency Virus Type 1 Vaccine Regimen Consisting of Consecutive Priming with DNA and Boosting with Recombinant Fowlpox Virus - Kent, Stephen J. (American Society for Microbiology, 1998)
The induction of human immunodeficiency virus (HIV)-specific T-cell responses is widely seen as critical to the development of effective immunity to HIV type 1 (HIV-1). Plasmid DNA and recombinant fowlpox virus (rFPV) vaccines are among the most promising safe HIV-1 vaccine candidates. However, the immunity induced by either vaccine alone may be insufficient to provide durable protection against HIV-1 infection. We evaluated a consecutive immunization strategy involving priming with DNA and boosting with rFPV vaccines encoding common HIV-1 antigens. In mice, this approach induced greater HIV-1-specific immunity than either vector alone and protected mice from challenge with a recombinant vaccinia virus expressing HIV-1 antigens. In macaques, a dramatic boosting effect on DNA vaccine-primed HIV-1-specific helper and cytotoxic T-lymphocyte responses, but a decline in HIV-1 antibody titers, was observed following rFPV immunization. The vaccine regimen protected macaques from an intravenous HIV-1 challenge, with the resistance most likely mediated by T-cell responses. These studies suggest a safe strategy for the enhanced generation of T-cell-mediated protective immunity to HIV-1.